Managerial control inside the firm - Shinichi Hirota; Kohei Kawamura (Osaka University, Institute of Social and Economic Research (ISER), 2005)
This paper proposes an implicit control mechanism of managers inside the firm. We argue that the need to motivate workers may make it beneficial for a self-interested, short-sighted manager to pursue long-run viability of the firm. When the firm is in a stable environment, this implicit control mechanism may not contradict shareholder value maximization. However, when the firm needs restructuring, this mechanism damages firm value. We discuss when external governance is desirable, and when it is not. Our model also offers economic explanations for some related issues in managerial behavior such as restructuring aversion, survival motive, and excessive risk aversion.
Keywords: G34; J41; 330; corporate governance; worker incentives; autonomous management; restructuring; corporate survival; managerial risk aversion; Corporate Governance; Leistungsmotivation; Leistungsanreiz; Organisatorischer Wandel; Management; Risikoaversion; Unternehmenswert